PROPOSTA DE CLASSIFICAÇÃO CLIMÁTICA DIÁRIA PARA AVALIAÇÃO DE DESEMPENHO EM MEDIÇÕES DE CAMPO - Rios, Rafael; Zanoni, Vanda (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
For building s studies, the classification of climate conditions are useful tools for design studies, performance evaluation. However, for a daily approach, such as building's surveys, there is a lack of methods for climate classification, which difficult the definition of test's parameters. So, based on the analysis of Typical Meteorological Year- TMY files from different Brazilian cities, this paper presents a method for daily weather classification. This method allows the daily weather characterization during building's survey, and also contributes for the definition of on field test's parameters.